Neural correlates of auditory cognition - Cohen, Yale E. (Springer handbook of auditory research, 2013)
since the early 1990s, there has been a re-birth of studies that test the neural correlates of auditory cognition with a unique emphasis on the use of awake, behaving animals as models. Continuing today, how and where in the brain neural correlates of auditory cognition are formed is an intensive and active area of research.  Importantly, our understanding of the role that the cortex plays in hearing has the potential to impact the next generation of cochlear- and brainstem-auditory implants and consequently help those with hearing impairments. This volume brings together this exciting literature on the neural correlates of auditory cognition. Auditory cognition: the integration of psychophysics with neurophysiology Yale E. Cohen Processing streams in auditory cortex Josef P. Rauschecker Task-related activation of auditory cortex Henning Scheich and Michael Brosch The role of auditory cortex in spatial processing Gregg H. Recanzone neural correlates of auditory object perception Jan W. H. Schnupp, Christian Honey, and Ben D. B. Willmore Neurophysiology of attention and memory processing Amy Poremba and James Bigelow Phonemic representations and categories Mitchell Steinschneider The influence of vision on auditory communication in primates Asif A. Ghazanfar and Chandramouli Chandrasekaran Attention and dynamic, Task-related receptive field plasticity in adult auditory cortex Jonathan B. Fritz, Stephen David, and Shihab Shamma Experience-dependent plasticity and auditory cortex Kathryn N. Shepard, Michael P. Kilgard, and Robert C. Liu   About the editors: Yale Cohen is Associate Professor of Otorhinolaryngology: Head and Neck Surgery and Neuroscience at The University of Pennsylvania, Philadelphia.  Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. Richard R. Fay is Distinguished Research Professor of Psychology atLoyola University Chicago. About the series: the springer sandbook of auditory research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.  . 1. Auditory cognition: The integration of psychophysics with neurophysiology -- 2. Processing streams in the auditory cortex -- 3. Task-related activation of the auditory cortex -- 4. The role of the auditory cortex in spatial processing -- 5. Neural correlates of auditory object perception -- 6. Neurophysiology of attention and memory processing -- 7. Phonemic representations and categories -- 8. The influence of vision on auditory communication in primates.-9. Attention and dynamic, task-related receptive field plasticity in adult auditory cortex -- 10. Experience-dependent plasticity and the auditory cortex - Kathryn N. Shepard, Michael P. Kilgard, Robert C. Liu.